2017
DOI: 10.1155/2017/2190897
|View full text |Cite
|
Sign up to set email alerts
|

Methane Suppresses Microglial Activation Related to Oxidative, Inflammatory, and Apoptotic Injury during Spinal Cord Injury in Rats

Abstract: Objective. We investigated the hypothesis that methane-rich saline (MS) can be used to repair spinal cord injury (SCI) in a rat model through suppressing microglial activation related to oxidative, inflammatory, and apoptotic injury. Methods. MS was injected intraperitoneally in rats after SCI. Hematoxylin-eosin (HE) staining, oxidative stress, inflammatory parameters, and cell apoptosis were detected 72 h after SCI to determine the optimal dose. Then, we investigated the protective mechanisms and the long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Pathological changes between CA and ROSC may be related to the degree of neurological dysfunction. Microglia, resident immune cells in the central nervous system (CNS), are increased in number and morphologically activated at an early stage after spinal cord injury [35,36], which contributes to neuroinflammation and onset of neuronal damage by releasing large amount of inflammatory cytokines and ROS [37,38]. Similar to previous studies, our results showed that ACA resulted in significant microglia activation in the ventral horn of the lumbar spinal cord.…”
Section: Discussionsupporting
confidence: 84%
“…Pathological changes between CA and ROSC may be related to the degree of neurological dysfunction. Microglia, resident immune cells in the central nervous system (CNS), are increased in number and morphologically activated at an early stage after spinal cord injury [35,36], which contributes to neuroinflammation and onset of neuronal damage by releasing large amount of inflammatory cytokines and ROS [37,38]. Similar to previous studies, our results showed that ACA resulted in significant microglia activation in the ventral horn of the lumbar spinal cord.…”
Section: Discussionsupporting
confidence: 84%
“…SCI is a serious neurological disease that can induce neurological dysfunction and permanent damage. Series of secondary injuries, including oxidative stress, mitochondrial dysfunction, and neuronal cell apoptosis, are considered as the major factor for disability [47]. Thus, new effective therapeutic treatments for reducing SCI-induced neurological disorders and tissue damages are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…It not only affects the physical and mental health of patients but is also an economic burden on the family [1][2][3]. At present, although various pharmacological therapies are used for SCI, functional recovery is still uncertain [4][5][6].…”
Section: Introductionmentioning
confidence: 99%